Covert communication performance evaluation in UAV-assisted rate-splitting multiple access systems - Nguyen Hong Nhu; Le Chi Bao; Bui Vu Minh; Minh Tran; Nguyen Quang Sang (PLoS ONE, 2025)
In this paper, we investigate using rate-splitting multiple access (RSMA) to facilitate covert communication in a multi-user unmanned aerial vehicle (UAV) downlink communication network that is being monitored by a warden (Willie). We establish a comprehensive analytical framework and derive closed-form expressions for key performance metrics under Nakagami-m fading channels. Specifically, we analyze the detection error probability (DEP) at Willie to quantify system covertness, in addition to outage probability (OP) and ergodic rate (ER) experienced by legitimate users, along with asymptotic analysis in the high signal-to-noise ratio (SNR) region. Furthermore, we propose an efficient alternating optimization algorithm to determine the optimal static position of the UAV that maximizes system covertness. Numerical simulations support the theoretical results derived, present the impact of various system parameters, and provide a performance comparison with non-orthogonal multiple access (NOMA). Results indicate that RSMA offers significant covertness gains over the NOMA scheme.